Management of comfort and sedation in neonates with neonatal encephalopathy treated with therapeutic hypothermia. Issue 4 (August 2021) - McPherson, Christopher; Frymoyer, Adam; Ortinau, Cynthia M.; Miller, Steven P.; Groenendaal, Floris; ,
Abstract: Ensuring comfort for neonates undergoing therapeutic hypothermia (TH) after neonatal encephalopathy (NE) exemplifies a vital facet of neonatal neurocritical care. Physiologic markers of stress are frequently present in these neonates. Non-pharmacologic comfort measures form the foundation of care, benefitting both the neonate and parents. Pharmacological sedatives may also be indicated, yet have the potential to both mitigate and intensify the neurotoxicity of a hypoxic-ischemic insult. Morphine represents current standard of care with a history of utilization and extensive pharmacokinetic data to guide safe and effective dosing. Dexmedetomidine, as an alternative to morphine, has several appealing characteristics, including neuroprotective effects in animal models; robust pharmacokinetic studies in neonates with NE treated with TH are required to ensure a safe and effective standard dosing approach. Future studies in neonates treated with TH must address comfort, adverse events, and long-term outcomes in the context of specific sedation practices.